AN ANALYSIS OF CLIMATE CHANGE IN THE UNITED STATES USING RECORD HIGH AND RECORD LOW TEMPERATURE DATA - Cundiff, Kirby R. (European Scientific Journal, ESJ, 2014)
To test climate change or global warming theories in the United States I analyzed record high and record low data for locations in all 50 of the United States for both January and July over the entire available record. While there was a general trend of increasing numbers of record highs and decreasing numbers of record lows, most of the regional results were not statistically significant and there were many counter trend examples. Of particular interest were the record highs during the extremely hot summers of the Great Depression in 1930s.